A Collaborative Self-Governing Privacy-Preserving Wireless Sensor Network Architecture Based on Location Optimization for Dynamic Service Discovery in MANET Environment. (18th August 2015) - Gao, Cong; Ma, Jianfeng; Zhang, Shangwei
Abstract : Due to the characteristics of a MANET, none of the existing solutions for service discovery work well in decentralized mobile environments. In this paper, we propose a collaborative self-governing privacy-preserving wireless sensor network architecture to address the issue of service discovery in MANET environment. The proposed architecture is able to dynamically adjust the working modes between directory-based and directory-less modes according to the network status of a MANET. The dynamic network status of a MANET is monitored by a wireless sensor network. Two location optimization algorithms are developed for topology control and the preservation of user location privacy. Simulation results show that the proposed architecture can greatly improve the performance of service discovery.